Waqf as a socio-economic institution - Haneef, Mohamed Aslam (King Abdulaziz University, 2018)
Syed Khalid Rashid’s lead paper titled ‘Potential of Waqf in Contemporary World’ is a welcome addition to the growing literature on waqf. This brief writeup focuses more on waqf as a ‘socio-economic institution’ and to place waqf as the ‘third’ or voluntary sector of the economy. It will raise some points on a variety of important‘issues’ essential for the revival of waqf which, it is hoped, will complement the lead article. In addition, this paper will share findings and draw from a research project (of which the author was a part of) on Waqf and Higher Education (termed as LRGSWaqf), to support arguments put forward.